Performance of silicon rubber coated polyetherimide hollow fibers for CO2 removal via a membrane contactor - Hashemifard, Seyed Abdollatif (Royal Society of Chemistry, 2015)
This study focuses on the effect of a silicon rubber coating technique on the hollow fiber membrane contactor for the purpose of CO2 removal. The polymer and the coating agent used were polyetherimide (PEI) and polydimethylsiloxane (PDMS) respectively. The hollow fibers were fabricated via a simple wet spinning technique. The surfaces of the hollow fibers were coated by means of PDMS dissolved in n-hexane applying different protocols. An effort was made to keep the silicon rubber coating layer porous. The membranes were characterized by applying a gas permeation test (GPT) via pure helium, critical entry pressure of water (CEPw), contact angle, a gas absorption test and scanning electron microscopy (SEM). Based on the observations, the coating technique resulted in drastic changes in the contact angle and CEPw of the coated membranes for the inside and outside coated hollow fiber membranes. Disregarding the method of coating and even the polymer concentration, the contact angle was enhanced dramatically. The CO2 absorption results revealed that by blowing nitrogen (600 kPa) through the lumen side of the hollow fibers during the PDMS coating process onto the outside surface, the absorption flux of the membranes was increased. A slight decrease in the CO2 absorption flux for the other cases was outweighed by a substantial enhancement in the membrane wetting resistance due to the high contact angle and CEPw. These observations showed the high influence of the silicon rubber layer on the CO2 gas absorption, which emphasizes the role of this key-parameter in controlling the ultimate membrane contactor performance.